PERAN EMPATI DAN KEPEDULIAN DALAM MENDUKUNG PENGEMBANGAN INTERAKSI SOSIAL DI MASYARAKAT MODERN - M. Fiqri Syahril; Elwas Berdha Krismona (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of empathy and caring in improving the quality of social interactions in modern society, characterized by digitalization, individualization, and changing communication patterns. This study uses a literature review method by reviewing ten national and international articles relevant to the themes of empathy, caring, prosocial behavior, and social interaction. The data collection process was carried out through article searches in various academic databases, followed by screening, eligibility selection, and content analysis. The analysis technique used was narrative synthesis to identify patterns, similarities, and differences in the findings of each study. The results show that empathy and caring have a significant influence on improving the quality of interpersonal relationships, strengthening social cohesion, and reducing social conflict, both in direct and digital interactions. Empathy has been shown to play a role as a basic ability to understand the emotional states of others, while caring encourages concrete actions in prosocial behavior. This study confirms that the development of social-emotional abilities is crucial for facing the increasingly complex dynamics of modern life.